Co-Administration of Amiodarone Increases Bleeding by Affecting Rivaroxaban Pharmacokinetics in Patients with Atrial Fibrillation - Huamin Ding; Zi Wang; Jia Wang; Yao Yao; Chi Zhang; Houwen Lin; Yong Zhou; Zhichun Gu; Qianzhou Lv; Xiaoye Li (MDPI AG, 2024)
This study aimed to investigate the impact of the drug-drug interaction between rivaroxaban and amiodarone on the clinical outcomes in patients with non-valvular atrial fibrillation (NVAF), focusing on pharmacokinetic and pharmacodynamic (PK/PD) aspects. A prospective study enrolling 174 patients with NVAF who were treated with rivaroxaban was conducted. The patients were divided into two groups based on postoperative antiarrhythmic and anticoagulation strategies: the rivaroxaban group (Control group) and the rivaroxaban plus amiodarone group (Riv/Amio group). The trough plasma concentrations (Ctrough) of rivaroxaban, activated partial thromboplastin time (APTT), prothrombin time (PT), and the clinical outcomes between the two groups were compared. Patients receiving 20 mg of rivaroxaban in the Riv/Amio group had a higher concentration of rivaroxaban Ctrough than those in the Control group (p = 0.009). Furthermore, in patients with moderate to severe renal impairment, rivaroxaban Ctrough was significantly increased in the Riv/Amio group. There was no significant difference in PT and APTT between the two groups. Regarding the clinical outcomes, the combination of rivaroxaban and amiodarone medication was associated with a higher incidence of bleeding events (p = 0.041; HR = 2.83, 95% CI 1.05-7.66) and clinically relevant non-major bleeding (p = 0.021; HR = 3.65, 95% CI 1.21-10.94). Finally, independent risk factors for bleeding in NAVF patients treated with rivaroxaban were identified as its combination with amiodarone (p = 0.044; OR = 2.871, 95% CI 1.028-8.023). The combination of rivaroxaban and amiodarone led to changes in rivaroxaban pharmacokinetics and an elevated risk of bleeding events. Therefore, physicians prescribing rivaroxaban medications should assess the potential bleeding risk associated with the concurrent use of amiodarone, particularly in patients with renal impairment.